Accounting for Calcareous Concretions in Calcic Vertisols Improves the Accuracy of Soil Hydraulic Property Estimations. Issue 6 (16th November 2017) - Gu, Feng; Ren, Tusheng; Li, Baoguo; Li, Lujiu
Abstract : Core Ideas: Calcareous concretions (CCs) could maintain a considerable amount of water and the water content of CCs decreased with an increase in CC sizes. The addition of CCs to soils changed the WRC and the pore distribution of soils significantly. The available water content (AWC) of soil–CC mixtures decreased when the CC content increased. A linear equation, which included CC content and CC water content, was proposed to estimate the AWC of soils containing CCs accurately. The soil water retention curve (WRC) is one of the most important properties in soil hydraulic studies. Current studies normally focus on fine soils, ignoring the water‐holding capacity of coarse fragments (>2 mm) and their effects on soil available water content (AWC). Calcareous concretions (CC) are coarse inclusions distributed widely in soils around the world. This study was conducted to quantify the effects of the proportion and size of CCs on the soil WRC and AWC of a calcic vertisol. The WRCs of CCs were measured using the sand box and ceramic plate method, and the WRCs of fine soils and soil–CC mixtures of various sizes (2–5, 5–8, and 8–30) and proportions (5, 10, 15, and 30% on a total mass basis) of CC were determined with the centrifuge method. The WRCs were fitted with the van Genuchten equation. The results showed that CCs retained a considerable amount of water. The saturated water contents of CCs of 2‐ to 5‐, 5‐ to 8‐ and 8‐ to 30‐mm were 0.251, 0.220, and 0.196 cm 3 cm –3, respectively. The addition of CCs changed the WRC and pore distribution of soils significantly. The AWC of soil–CC mixtures decreased with increasing CC content. A linear equation, which included the fraction of CCs and water content in CCs, was proposed to estimate the AWC of soils containing CCs accurately. Accounting for CCs in the calcic vertisol improved the accuracy of soil hydraulic property estimations.